1977
DOI: 10.1179/bjo.4.2.53
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Maxilla in Three Dimensions as Revealed Radiographically by the Implant Method

Abstract: By use of the implant method the growth of the maxilla was analysed from profile and frontal (postero-anterior) cephalometric radiographs in nine boys with normal primary occlusion who were followed annually up to adult age without receiving any orthodontic treatment. The proportion of sutural and appositional growth in height was determined from profile radiographs with reference to implants in the infrazygomatic crest. The sutural lowering of the maxillary corpus was, on average, about twice as big as the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
171
0
16

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(205 citation statements)
references
References 14 publications
18
171
0
16
Order By: Relevance
“…During superimposition, particular attention was given to fitting the tracings of the cribriform plate and the anterior wall of the sella turcica which undergo minimal remodelling. 17 Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…During superimposition, particular attention was given to fitting the tracings of the cribriform plate and the anterior wall of the sella turcica which undergo minimal remodelling. 17 Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…O autor descreveu o método estrutural, no qual é possível predizer, a partir de uma úni-ca telerradiografia, a tendência de crescimentos rotacionais extremos, baseando-se em sete sinais estruturais, a inclinação do côndilo, a curvatura do canal mandibular, a forma da borda inferior da mandíbula, a inclinação da sínfise, o ângulo interincisivos e interpré-molares e a altura facial ântero-inferior. Com os trabalhos desenvolvidos posteriormente por Skiller 10,11 , os princípios descritos sedimentaram-se.…”
Section: Bjorkunclassified
“…1,9,[15][16][17] The results of the longitudinal growth studies have shown that due to the apposition in the glabella region, nasion moves forward in an upward or downward direction throughout the whole growth period due to the individual growth pattern. 18,19 If nasion moves in a downward direction, then the inclination of the sella-nasion line (cranial base) will change, and this would lead to a more obtuse SNA angle. In the present study, nasion might have moved in a forward, however mainly in a downward direction during the treatment, so the posterior movement of point A could not lead to a significant decrease in SNA angle.…”
Section: 35-10mentioning
confidence: 99%